Transporting operations of food materials within food factories - Jafari, Seid Mahdi; Malekjani, Narjes (Unit operations and processing equipment in the food industry., 2023)
"Explains the processing operations and equipment necessary for storage and transportation of food materials within food production factories. Divided into four sections, Receiving and storage facilities, Liquid food transportation, Solid and semi- solid transportation and General material handling machines in food plants, all sections emphasize basic content relating to experimental, theoretical, computational and/or applications of food engineering principles and relevant processing equipment" --